2018
DOI: 10.3390/econometrics6010005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing News Contagion in Finance

Abstract: Abstract:The analysis of news in the financial context has gained a prominent interest in the last years. This is because of the possible predictive power of such content especially in terms of associated sentiment/mood. In this paper, we focus on a specific aspect of financial news analysis: how the covered topics modify according to space and time dimensions. To this purpose, we employ a modified version of topic model LDA, the so-called Structural Topic Model (STM), that takes into account covariates as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…More data can offer other types of information not available in the data at hand. Moreover the application of other text analysis technique like topic modeling (Cerchiello and Nicola, 2018) rather than the creation of manual dictionaries to make the process more automated and therefore decrease the time spent in preprocessing, can improve even more the quality of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…More data can offer other types of information not available in the data at hand. Moreover the application of other text analysis technique like topic modeling (Cerchiello and Nicola, 2018) rather than the creation of manual dictionaries to make the process more automated and therefore decrease the time spent in preprocessing, can improve even more the quality of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the second option is rarely feasible because in order to fit a good classifier, a huge amount of pre-classified examples is needed and this represents a particularly complicated task when dealing with short and extremely non conventional text like micro-blogging chats (Cerchiello and Nicola, 2018). Insofar, we decided to focus on a dictionary based approach, adapting appropriate lists of positive and negative words relevant to ICOs topics in English language.…”
Section: Methodsmentioning
confidence: 99%
“…Social media is rapidly replacing non-digital media as a convenient and fast medium for communicating and sharing information, allowing users to interactively express their one-sided views on the housing market. The role of social media in sentiment detection has received increasing attention from researchers (Cerchiello & Nicola, 2018). Social media data have the characteristics of full samples, high frequency, and immediacy, and a sentiment index based on social media data is highly representative and forward-looking (Da et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, existing housing-related research on market sentiment is seriously lacking, most existing studies have relied on indirect indicators such as relatively lagging macroeconomic data, and the use of social media data, which can indicate the public's immediate attitudes toward the latest information, is still uncommon. The impact of this data source on home-buyer sentiment is evident in the modern information society (Cerchiello & Nicola, 2018). Sinyak et al (2021) found that social media of the real estate market can be considered a valuable and innovative source of market sentiment and can provide real estate researchers and valuers with reliable leading market indicators.…”
Section: Literature Reviewmentioning
confidence: 99%